2015
DOI: 10.1002/aenm.201500188
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Prospects in Symmetrical Solid Oxide Fuel Cells with Two Identical Electrodes

Abstract: The increasing impact of the greenhouse effect and environmental pollution from excessive and low-effi ciency use of everdiminishing fossil fuels has urged us to develop new energy materials and technologies for transitioning to a sustainable infrastructure. With this in mind, fuel cells, based on a concept Symmetrical solid oxide fuel cells (SOFCs) have attracted increasing attention due to their potential for improved thermomechanical compatibility of the electrolyte and the electrodes, reduced fabrication c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 176 publications
(381 reference statements)
0
96
0
1
Order By: Relevance
“…Limited materials have been reported to be effectively used as both anode and cathode for SSOFCs [7]. Conventional ceramic anode materials as electrodes for SSOFC showed poor cathode performance, and consequent low fuel cell output [4,[8][9][10][11],…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Limited materials have been reported to be effectively used as both anode and cathode for SSOFCs [7]. Conventional ceramic anode materials as electrodes for SSOFC showed poor cathode performance, and consequent low fuel cell output [4,[8][9][10][11],…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, a new conguration of SOFCs, in which the same material is used for both electrodes, was proposed, and the corresponding fuel cells were called symmetrical SOFCs. [8][9][10][11][12][13][14][15][16] In fact, with low-temperature polymer-electrolyte-membrane fuel cells, the anode and cathode are oen fabricated from the same Pt/C-based catalyst, although they may contain different Pt contents. 17,18 The adoption of the same material composition for both electrodes in SOFCs can bring several benets, such as reduced fabrication cost and increased cell stability, as well as enabling facile cell regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The adoption of the same material composition for both electrodes in SOFCs can bring several benets, such as reduced fabrication cost and increased cell stability, as well as enabling facile cell regeneration. [8][9][10][11][12][13][14][15][16] Therefore, recently, an increased interest in the development of symmetrical SOFCs has been envisioned.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, it was found that a much better stability can be achieved by SOFCs which operate in both SOFC and solid oxide electrolytic cell (SOEC) modes (reversible SOFC)2. For reversible SOFCs, the use of a symmetrical electrode such as (La 0.75 Sr 0.25 )Cr 0.5 Mn 0.5 O 3−δ (LSCM) would be an ideal solution345. An essential requirement of the electrode material is that it must exhibit a high conductivity in both air and fuel conditions at the fuel cell operating temperature.…”
mentioning
confidence: 99%